Comparison of fks gene mutations and minimum inhibitory concentrations for the detection of Candida glabrata resistance to micafungin: A systematic review and meta‐analysis. Issue 9 (9th June 2019) - Bienvenu, Anne‐Lise; Leboucher, Gilles; Picot, Stephane
Summary: Candida resistance to antifungals impaired invasive candidiasis outcome. In a context of echinocandin resistance development, we aimed to evaluate the association between phenotypic resistance to micafungin and fks mutations of Candida glabrata . For this systematic review and meta‐analysis, we searched MEDLINE, Scopus and Web of Science for reports published up to December 2017. Studies of C glabrata candidiasis with minimum inhibitory concentrations (MIC) determination of micafungin and fks genotyping were included. Reviews, studies not using reference methods, non‐ glabrata Candida, experimental isolates and undetailed mutations were excluded. Two authors independently assessed the eligibility of articles and extracted data. The main outcome was the diagnostic accuracy of fks mutations compared to micafungin MIC for C glabrata, measured as fixed‐effect odd ratio. Heterogeneity was calculated with the I 2 statistic. This study is registered with PROSPERO (CRD42018082023). Twenty‐four studies were included in the meta‐analysis. Pooled analysis found that S663P (OR 7.25, 95% CI 3.50‐15.00; P  < 0.00001), S629P (OR 3.70, 1.64‐8.33; P  = 0.002) and F659del (OR 5.66, 1.22‐26.18; P  = 0.03) were associated with increased risk of having a resistant isolate according to authors' interpretation of MICs. In sensitivity analysis based on new CLSI clinical breakpoints, the ORs for S663P and S629P remained significant. Genotyping of isolates of C glabrata for S663P and S629P mutations is an effective alternative to micafungin susceptibility tests. Relevant molecular markers of drug resistance will significantly improve the management of C glabrata infections.